2016
DOI: 10.1158/0008-5472.can-15-2813
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell Invasion Can Be Blocked by Modulators of Collagen Fibril Alignment That Control Assembly of the Extracellular Matrix

Abstract: Abnormal architectures of collagen fibers in the extracellular matrix (ECM) are hallmarks of many invasive diseases, including cancer. Targeting specific stages of collagen assembly in vivo presents a great challenge due to the involvement of various crosslinking enzymes in the multistep, hierarchical process of ECM build-up. Using advanced microscopic tools, we monitored stages of fibrillary collagen assembly in a native fibroblast-derived 3D matrix system and identified anti-lysyl oxidase-like 2 (LOXL2) anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 46 publications
7
86
1
Order By: Relevance
“…The artificial vessel ring collagen was detected using second harmonic generation (SHG) microscopy, and VSMCs were stained for α SMA (A2547 Sigma‐Aldrich, St. Louis, MO, USA) and then imaged (Jena Germany) as described (Grossman et al., 2016). Volocity image analysis software (Perkin Elmer, Waltham, MA, USA) was then used to segment the VSMCs in 3D based upon a‐SMA staining and calculate the respective parameters of VSMCs automatically with the captured 3D cell images (Porter, Holt, Soong, Shanahan & Warren, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The artificial vessel ring collagen was detected using second harmonic generation (SHG) microscopy, and VSMCs were stained for α SMA (A2547 Sigma‐Aldrich, St. Louis, MO, USA) and then imaged (Jena Germany) as described (Grossman et al., 2016). Volocity image analysis software (Perkin Elmer, Waltham, MA, USA) was then used to segment the VSMCs in 3D based upon a‐SMA staining and calculate the respective parameters of VSMCs automatically with the captured 3D cell images (Porter, Holt, Soong, Shanahan & Warren, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Imaging analysis for collagen directionality was done by Fiji package (Schindelin et al., 2012). Fourier component analysis for directionality was performed on data using the Fiji plug‐in “Directionality” and following manufacturer's instructions (Grossman et al., 2016). …”
Section: Methodsmentioning
confidence: 99%
“…Additional studies revealed that collagen fiber alignment can predict cell motility, relative to the pore size and density (Fraley et al 2015), and that an increase in protrusion frequency, persistence, and lengthening along the direction of the fibers depends on FAK and Rac1 signaling (Carey et al 2016). Indeed, preventing collagen alignment by inhibiting the activity of the collagen cross-linker LOXL2 (Grossman et al 2016), or through knockdown of the proteoglycan syndecan1 (Yang et al 2011), but not by inhibiting protease activity (matrix metalloproteinases [MMPs] and serine and cysteine proteases), reduced the directional migration of tumor cells in vitro and in vivo (Wyckoff et al 2006;Levental et al 2009;Rubashkin et al 2014). Thus compelling in vitro and in vivo data attest to the importance of alignotaxis as a regulator of the local invasion of tumor cells.…”
Section: Alignotaxismentioning
confidence: 99%
“…For instance, inhibition of LOX through pharmacological inhibition or injection with lysyl oxidase (LOX)-neutralizing antibodies reduced tumor metastasis from solid tumors (Levental et al 2009;Cox et al 2013;Pickup et al 2013). Similarly, studies using function-blocking antibodies to inhibit lysyl oxidase-like 2 (LOXL2) reduced collagen alignment and decreased tumor burden in a breast tumor xenograft (Grossman et al 2016); these antibodies have been associated with invasiveness and poor outcome in breast cancer (Ahn et al 2013). Higher LOXL2 levels are also associated with tumor invasion and poor outcome in pancreatic cancer patients and showed some efficacy in mouse models of PDAC (Park et al 2016).…”
Section: Disrupting the Gradientmentioning
confidence: 99%
“…This limitation is problematic because fibers may play important roles in directing cell behavior; for example, fibrillar alignment of collagen in breast tumors has been shown to correlate with a worse patient prognosis [31, 32]. The influence of fibrillar structure on cellular outcomes was also highlighted by recent work which described a significant decrease in mouse xenograft tumor growth upon attenuation of fiber formation and crosslinking by inhibition of LOXL2 [33]. Here, we report a novel method for fabricating an interpenetrating network (IPN) hydrogel of gelMA and collagen I which allows for a wide variation of shear modulus while retaining the fibrillar structure of collagen.…”
Section: Introductionmentioning
confidence: 99%